THE PLIGHT OF NAMBOODIRI WOMEN IN COLONIAL KERALA – READING THROUGH LALITHAMBIKA ANTHARJANAM’S CAST ME OUT IF YOU WILL - Sabitha M.M (Research Scholar, 2014)
Lalithambika Antharjanam, the First Woman of Malayalam Letters and the lone voice from the elite Namboodiri community of Kerala, played an important role in the social transformation of the community and of Kerala society in general. This paper intends to study an anthology of her short stories and memoirs, Cast Me Out If You Will, translated by Geetha Krishnankutty. These stories are not totally fictional; rather they are the true historical representation of the life of Namboodiri women who were condemned to lead a cloistered life beset with tormenting taboos. During the colonial era, Namboodiris were at the top of Kerala’s traditional social hierarchy. But the community degenerated due to the indulgence of Namboodiri men in multi marriages and uninhibited lifestyles, while their wives lived in seclusion being away from the outside world. Antharjanam’s writings captured the spirit of the period and the struggle of the then young generation. Her famous short stories explicit the suffocation of Namboodiri women, their struggle in a hostile world, their loneliness and their search for an identity of their own. These stories unfold the turbulent life of these Protagonists, and the brutal suppression suffered by them and how they are excommunicated or incarcerated from their community due to their rebellious reactions to the patriarchal society